Potential for Prebiotics as Feed Additives to Limit Foodborne Campylobacter Establishment in the Poultry Gastrointestinal Tract - Kim, Sun Ae; Jang, Min Ji; Kim, Seo Young; Yang, Yichao; Pavlidis, Hilary O.; Ricke, Steven C. (Frontiers in Microbiology, 2019)
Campylobacter as an inhabitant of the poultry gastrointestinal tract has proven to be difficult to reduce with most feed additives. The use of in-feed antibiotics have been taken out of poultry diets due to the negative reactions of consumer along with concerns regarding the generation of antibiotic resistant bacteri. Consequently, interest in alternative feed amendments to antibiotics has grown. One of these alternatives, prebiotics has been examined as a potential animal and poultry feed additive. Prebiotics are non-digestible ingredients that enhance growth of indigenous gastrointestinal bacteria that elicit metabolic characteristics which are considered beneficial to the host. In addition, these compounds support microbial activities in the gastrointestinal tract that are antagonistic to the establishment of pathogens. There are several carbohydrate polymers that qualify as prebiotics and have been fed to poultry. These include mannoligosaccharides and fructooligosaccharides as the most common ones marketed commercially that have been used as feed supplements in poultry. More recently several non-digestible oligosaccharides have also been identified as possessing prebiotic properties when implemented as feed supplements. While prebiotics appear to be generally effective in poultry and limit establishment of foodborne pathogens such as Salmonella in the gastrointestinal tract, less is known about their impact on Campylobacter. This review will focus on the potential of prebiotics to limit establishment of Campylobacter in the poultry gastrointestinal tract and future research directions.